Does the position in the inter-sectoral knowledge space affect the international competitiveness of industries? - Francesco Lamperti; Franco Malerba; Roberto Mavilia; Giorgio Tripodi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
This paper empirically investigates how the inter-sectoral knowledge flows affect the international competitiveness of industries, once controlling for both cost and other technological factors. Using patent data on 14 manufacturing industries in 16 OECD countries over the period 1995-2009, we apply a network-based approach to capture the effect of industries' position in the flows of technological knowledge across industries, which we label inter-sectoral knowledge space. We find that (i) centrality and local clustering in the inter-sectoral knowledge space positively affect the export market shares of an industry, (ii) such two effects are rather redundant and, (iii) national-level knowledge flows' impacts on international competitiveness are way stronger than international ones. Network measures of position in the knowledge space are found to be more relevant than standard technological indicators such as patent counts. Our results point to the importance of industries being well located in the stream of knowledge flows, rather than being innovative per-se, and offers an novel yet robust proxy to measure technological factors affecting trade performances. In addition, we find evidence of geographical boundaries of knowledge flows.
Keywords: D85; F14; L60; O3; 330; international trade; industry competitiveness; knowledge flows; patent data